KINERJA SUBSURFACE CONSTRUCTED WETLAND MULTYLAYER FILTRATION TIPE ALIRAN VERTIKAL DENGAN MENGGUNAKAN TANAMAN AKAR WANGI (Vetivera Zozanoides) DALAM PENYISIHAN BOD DAN COD DALAM AIR LIMBAH KANTIN - Ariani Dwi Astuti; Muhammad Lindu; Ramadhani Yanidar; Maria Manda Kleden (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2016)
Wastewater from the canteen is a domestic wastewater that has high concentrations of organic matter that needs to be processed before being released and not contaminating the water stream. The wastewater treatment at canteen SMA Negeri 34 Jakarta begins with collecting basin and aeration basin, and then it is pumped into two reactor that is the subsurface constructed wetland multilayers filtration type flow vertical with Vetiver Grass unit (SCW-MLF) and multilayers filtration type flow vertical unit without plants (MLF) as a control. The purpose of this study was to test the effectiveness of the vetiver grass in wastewater treatment with subsurface constructed wetland unit multilayers filtration type vertical flow with vetiver grass to fulfill effluent standards before it is released into stream water. Metodology of the study was conducted from acclimatization of plants, removal the plant to the SCW-MLF unit, and analyze the quality of wastewater. Flowrate that goes into the processing unit is 6.9615 m3/day. The detention time in SCW-MLF unit was 17.7 hours. The results showed that at steady state COD organic loading on SCW-MLF unit is 917.08 to 4126.84 kg COD/ha/day for the removal efficiency around 69.2 to 80.0%, BOD organic loading is 309.78 to 850,73 kg BOD/ha/day for the removal efficiency 61.2 to 70.8%. K value SCW-MLF unit around 0.55 to 0.71 m/day for BOD, 0.57 to 0.89 m /day for COD. The concentration of the wastewater effluent from WWTP are complied to effluent standart regulation (Pergub DKI Jakarta No. 112 Tahun 2005).